DIFFERENCE OF THE RIGHT OF HOUSING INTEGRITY FROM SOME RELATED RIGHTS (World Bulletin of Management and Law, 2024)
This article examines the essence of the right to the inviolability of the home, and identifies the subjects of this right. A comparative legal analysis of the right to privacy of housing with the right to housing, the right to privacy, and the right to inviolability of property was carried out.